Design and Implementation of IOT-Based Monitoring System on Nanobubble-Based Hydroponics Farming - Mutia Safira; Asep Yusuf; Taufik Ibnu Salim; Hilman Syaeful Alam (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Maintaining Dissolved Oxygen (DO) levels in the hydroponic plant nutrient solutions can be done using nanobubble technology. Manual monitoring can be time-consuming and measurement results are less accurate. Therefore, a monitoring system is needed to monitor air temperature, air humidity, water temperature, water pH, nutrient concentrations, and DO levels. Several stages in this research are preparation, design, sensor calibration, and monitoring system implementation. Air temperature and humidity conditions can be measured with the DHT22 sensor, water temperature can be measured with the DS18B20 sensor, water pH can be measured with the Analog pH Meter Pro, nutrient density can be measured with the Analog TDS sensor, and DO levels can be measured with the Dissolved Oxygen Sensor. Based on the measurement results monitored by the monitoring system, the parameters that affect the ignition of the nanobubble generator are DO values and water temperature. The system can also visualize sensor data on monitors and online, and can store sensor data locally and IoT so that this system has the potential to monitor hydroponics, especially nanobubble-based hydroponics. Keywords:   Sensor, Dissolved Oxygen, Arduino Uno, ESP32-E, NodeMCU ESP8266